Acute effects of scapular Kinesio Taping® on shoulder rotator strength, ROM and acromiohumeral distance in asymptomatic overhead athletes - Harput, G.; Guney, H.; Toprak, U.; Colakoglu, F.; Baltaci, G. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: There is limited information in the literature that shows whether scapular taping has an effect on the acromiohumeral distance (AHD) and shoulder functions. The aim of this study was to investigate the acute effects of scapular Kinesio Taping® on shoulder internal rotation (IR) and external rotation (ER) strength, IR and ER range of motion (ROM) and AHD in asymptomatic overhead athletes.